A NOVEL LANGERIN EXPRESSING TYPE 2-CONVENTIONAL DENDRITIC CELL IS SIGNIFICANTLY DECREASED IN CROHN'S DISEASE. (21st January 2021) - Doyle, Chloe; Bertram, Kirstie; Rhodes, Jake; Cunningham, Anthony; Ctercteko, Grahame; Byrne, Scott; Harman, Andrew
Abstract: Crohn's disease is a chronic relapsing auto-inflammatory condition of the gastrointestinal tract that primarily affects young individuals with an increasing incidence rate. There is still no cure for Crohn's disease and current treatment-options are limited to controlling inflammatory molecules such as TNF. Unfortunately, these biologics can produce significant side effects and not all patients respond to anti-TNF treatment. New treatments are therefore urgently needed. Targeting the cells and molecules of the immune system still represents the most promising approach which is why we have conducted an in-depth study of the immune cells and molecules associated with a healthy intestinal immune system and compared that to what is happening in Crohn's disease. Our group has privileged access to large human ileum explants as well as draining lymph node samples isolated from patients undergoing colorectal surgery to remove Crohn's affected tissue. We have designed and optimised enzymatic tissue digestion protocols to isolate these cells in an immature state with minimal receptor cleavage. We have also developed high-parameter flow and mass cytometry panels to comprehensively identify and characterise all known subsets of mononuclear phagocytes (MNP), innate lymphoid cells, mucosal-associated invariant T cells, natural killer cells and T and B lymphocytes. We have discovered that the newly described Langerin + type 2-conventional dendritic cell (cDC2) is significantly decreased in Crohn's affected ileum compared to healthy ileum. Furthermore, we have shown this decrease corresponds with lower TGF-b levels, a known driver of Langerin expression. After 7 days of co-culture, sorted Langerin + cDC2 induced significantly higher levels of IL-17 and IL-22 in allogenic naïve CD4 + T cells compared to other MNP subsets, including cDC2 which did not express Langerin. These differentiated T cells expressed high levels of RORt and aryl hydrocarbon receptor (AHR) – transcription factors that are associated with CD4 + T helper 17 cells, implying that they may play a crucial role in intestinal barrier repair and regeneration that is absent in Crohn's disease. Together these results suggest that Langerin + cDC2 may have an anti-inflammatory role in human tissue and their reduction in Crohn's disease may contribute to the pathogenesis of this disease, highlighting a potential therapeutic target for Crohn's disease.